MicroRNAs Modulate Interactions between Stress and Risk for Cocaine Addiction - Doura, Menahem B.; Unterwald, Ellen M. (Frontiers in Cellular Neuroscience, 2016)
Exposure to stress increases vulnerability to drug abuse, as well as relapse liability in addicted individuals. Chronic drug use alters stress response in a manner that increases drug seeking behaviors and relapse. Drug exposure and withdrawal have been shown to alter stress responses, and corticosteroid mediators of stress have been shown to impact addiction-related brain function and drug-seeking behavior. Despite the documented interplay between stress and substance abuse, the mechanisms by which stress exposure and drug seeking interact remain largely unknown. Recent studies indicate that microRNAs (miRNA) play a significant role in stress modulation as well as addiction-related processes including neurogenesis, synapse development, plasticity, drug acquisition, withdrawal and relapse. MiRNAs are short non-coding RNAs that function as bidirectional epigenetic modulators of gene expression through imperfect sequence targeted degradation and/or translational repression of mRNAs. They serve as dynamic regulators of CNS physiology and pathophysiology, and facilitate rapid and long-lasting changes to complex systems and behaviors. MiRNAs function in glucocorticoid signaling and the mesolimbic dopamine reward system, as well as mood disorders related to drug withdrawal. The literature suggests miRNAs play a pivotal role in the interaction between exposures to stress, addiction-related processes, and negative affective states resulting from extended drug withdrawal. This manuscript reviews recent evidence for the role of miRNAs in the modulation of stress and cocaine responses, and discusses potential mediation of the interaction of these systems by miRNAs. Uncovering the mechanism behind the association of stress and drug taking has the potential to impact the treatment of drug abuse and prevention of relapse. Further comprehension of these complex interactions may provide promising new targets for the treatment of drug addiction.